Electron Impact Ionization Cross Sections of Allene and Propane Molecules at Low and High Energy Range (Journal of Atomic and Molecular Sciences, 2012)
We have made a study of the total ionization cross sections of hydrocarbon molecules (allene, propane) due to electron impact for single ionization. Electron impact ionization cross sections (EIICS) have been calculated from threshold ionization energy to high energy (10 MeV). Along with EIICS calculation the values of collisional parameters are also calculated. The theoretical model, developed by Khare, has been modified to calculate the electron impact ionization cross section for molecules and atoms. The predicted EIICS of allene and propane molecules are compared with other theoretical and experimental data. Present model prevail a high degree of goodness of cross sections to the experimental data.  Adequate comparisons of collisional parameter have been made with other available experimental values.